Platformization and Informality Pathways of Change, Alteration, and Transformation - Surie, Aditi; Huws, Ursula (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
In this edited volume, scholars from Mumbai, Bengaluru, Jakarta, Cape Town, Sao Paulo and other cities of the global South explore the complex relationship between platformization and informality through a different lens. Drawing on extensive theoretical, quantitative and qualitative scholarship, they provide both a useful overview and insights into the lived realities of gig work for platforms covering a range of skills, working conditions, and forms of algorithmic management. Platform work has attracted considerable attention from scholars in the global North, who have tended to view it as a form of casualisation of work that was previously regulated. But what about the global South, where most employment, especially that of women and migrant workers was historically already informal? Beyond a focus on livelihoods, employment, and work, the authors show how labour platforms take on powers that bring about broader impacts, including those affecting identity and personal wellbeing. They also illustrate the impact of platformization on the governance of affected sectors by public agencies, thus affecting political power, and how public data infrastructures contribute to further platformization. The purpose of this pioneering work is to lay bare these interactions to then rebuild our understanding of platformization and its social, political, cultural and economic impacts. Its insights are attentive to gender and ethnic differences, as well as geographical ones. Aditi Surie is a Researcher at the Indian Institute for Human Settlements, Bengaluru, India where she studies technology, capitalism and metropolitan economies of the global South. Ursula Huws has held professorial positions at London Metropolitan University and the University of Hertfordshire, UK, and is now working independently. She has been researching the economic and social impacts of technological change, the restructuring of employment and the changing international division of labour since the 1970s.
1.Platformization and Informality: Pathways of Change, Alteration, and Transformation -- 2.Platformizing Informality, One Gig at a Time.-3.Work on Online Labour Platforms: Does Formal Education Matter -- 4.(In)Formality and the Janus Face of the Platform: Production of the 'Space of Taxi Driving' between Everyday Realities and Rationalities of State and Market -- 5.Uberization: The Periphery as the Future of Work? -- 6.Gojek as Labour Infrastructure: Platformization of Work in Indonesia -- 7.Feminist Approaches to Location-Based Labour Platforms in India -- 8 Metaphors of Work, from 'Below' -- 9. (Re)Conceptualizing Gendered Structures of Informality for Domestic Workers in the Platform Economy .
Keywords: Industrial sociology; Mass media; Science -- Social aspects; Digital media; Sociology of Work; Media Sociology; Science and Technology Studies; Digital and New Media